RUNX1/CD44 axis regulates the proliferation, migration, and immunotherapy of gliomas: A single-cell sequencing analysis - Zhang, Hao; Cao, Hui; Luo, Hong; Zhang, Nan; Wang, Zeyu; Dai, Ziyu; Wu, Wantao; Liu, Guodong; Xie, Zongyi; Cheng, Quan; Cheng, Yuan (Frontiers in Immunology, 2023)
Background: Glioma is one of the most common, primary, and lethal adult brain tumors because of its extreme aggressiveness and poor prognosis. Several recent studies relevant to the immune function of CD44, a transmembrane glycoprotein as a significant hyaluronic acid receptor, have achieved great success, revealing the critical role of CD44 in immune infiltration in gliomas. The overexpression of CD44 has been verified to correlate with cancer aggressiveness and migration, while the clinical and immune features of CD44 expression have not yet been thoroughly characterized in gliomas. Methods: Molecular and clinical data of glioma collected from publicly available genomic databases were analyzed. Results: CD44 was up-expressed in malignant gliomas, notably in the 1p/19q non-codeletion cases, isocitrate dehydrogenase (IDH) wild-type, and proneural subtypes in GBM samples. Intra-tumor heterogeneity has been found in CD44 expression, and higher CD44 expression was in the cellular tumor, leading edge regions. Enrichment of CD44 in a variety of immune regulatory processes was detected by gene ontology and pathway analysis, such as helper 2 T cell differentiation in GBM. CD44 expression level strongly correlates with stromal and immune cells, mainly infiltrating the glioma microenvironment by single-cell sequencing analysis. Meanwhile, CD44 can be a promising biomarker in predicting immunotherapy responses and mediate the expression of PD-L1. Finally, RUNX1/CD44 axis could promote the proliferation and migration of gliomas. Conclusions: Therefore, CD44 was responsible for glioma growth and progression. It could potentially lead to a novel target for glioma immunotherapy or a prognostic biomarker.